Environmental-economic accounting for water: a global comparative analysis (Sustainability in Debate, 2024)
Water accounts emerge to express their physical volume in the environment and the economy, as well as the economic aspect of water supply and use. Therefore, it enables public policymakers to make the most appropriate decisions for its management. So, the research objective is to analyse how different countries disclose their environmental and economic accounts for water. Therefore, a categorical analysis model of 120 categories was developed based on the SEEA-Water framework and analysed in 13 countries. The results highlight the high adherence to the physical water supply and use tables. It is interpreted as a “starting point” for compiling water accounts. Despite this, water emission accounts have not been prioritised, possibly due to data unavailability. Both hybrid and asset accounts are in progress. Concerning the countries, Brazil, Mexico, and Costa Rica achieved the highest adequacy level for the proposed model.